2018
DOI: 10.1177/0954411918796534
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and experimental study of effective parameters on process temperature during cortical bone drilling

Abstract: Bone drilling process is a prominent step of internal fixation in orthopedic surgeries. Process forces, leading to chip production, produce heat in the vicinity of the drilled bore and increase the probability of necrosis phenomenon. In this article, an analytical model to predict process temperature is presented based on Sui and Sugita model. This heat transfer model is the combination of a heat equilibrium equation for tool-chip system and a heat distribution equation for the bone itself where heat generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…However, it is a general acceptance that force regulates the heat generation in bone drilling; increasing force elevates bone temperature. 88,167,175,176 Others discovered a significant influence of point angle on bone damage, but the findings are contradictory. For example, the first group unveiled that a larger point angle increases bone temperature 10,21,102,115,123,147,162,167,175,176 and force.…”
Section: Point Anglementioning
confidence: 99%
“…However, it is a general acceptance that force regulates the heat generation in bone drilling; increasing force elevates bone temperature. 88,167,175,176 Others discovered a significant influence of point angle on bone damage, but the findings are contradictory. For example, the first group unveiled that a larger point angle increases bone temperature 10,21,102,115,123,147,162,167,175,176 and force.…”
Section: Point Anglementioning
confidence: 99%
“…When i = j, the x i x j term converts to x 2 i the square of main input parameters, and when i 6 ¼ j, the x i x j term is the second-order interaction of the input parameters. 20 An accurate regression model can signify the behavior of the output variable in the range of the experimentation and it can give the optimum condition of machining. 21…”
Section: Rsmmentioning
confidence: 99%
“…Abouzgia et al [7] studied the bone drilling process, without a cooling system, on the bovine bone with the rotational speed of up to 49,000 rpm reported that speed rise, up to 40,000 rpm, can cause lower temperatures and shorter recovery periods. Heydari et al [8] stated that in lower feed rates, higher temperatures are expected due to 1) further contact between drilling tool and bone and 2) increased thrust forces. Singh et al [9] studied mainly focuses on optimization of drilling parameters like rotational speed, feed rate, and the type of tool and observed that on increasing the rotational speed, the measured surface roughness was decreasing.…”
Section: Introductionmentioning
confidence: 99%